2022
DOI: 10.3390/ijms23126681
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Preparation of Tannic Acid Carbon Dots for Selective Detection of Ni2+ in the Environment

Abstract: Carbon dots (CDs) are widely used nanomaterials that not only exhibit good biocompatibility and photostability, but also benefit from a simple preparation process and easy functionalization, making them promising for broad applications in the fields of heavy metal ion detection and optoelectronic devices. Based on the excellent optical properties of CDs and the current situation of increasing energy shortages, this paper selects the natural polyphenolic compound tannic acid (TA) found in biomass materials as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In the ultraviolet absorption region, both the Y-CDs and G-CDs exhibit significant absorption peaks at 251 nm and 284 nm. The absorption peak at 251 nm corresponds to the π-π* transition of the C=C bond in the carbon nucleus, while the absorption peak at 284 nm corresponds to the n-π* transition of the C=C bond in the carbon nucleus [ 13 ]. In addition, distinct from the UV-Vis absorption spectra of Y-CDs and G-CDs, we observed that there was a characteristic absorption peak at 276 nm in the spectra of B-CDs, which corresponds to the B-absorption peak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ultraviolet absorption region, both the Y-CDs and G-CDs exhibit significant absorption peaks at 251 nm and 284 nm. The absorption peak at 251 nm corresponds to the π-π* transition of the C=C bond in the carbon nucleus, while the absorption peak at 284 nm corresponds to the n-π* transition of the C=C bond in the carbon nucleus [ 13 ]. In addition, distinct from the UV-Vis absorption spectra of Y-CDs and G-CDs, we observed that there was a characteristic absorption peak at 276 nm in the spectra of B-CDs, which corresponds to the B-absorption peak.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have gradually discovered that CDs have exceptional properties, including low toxicity, antibleaching, good biocompatibility [ 2 , 3 , 4 ], and excellent photostability [ 5 , 6 , 7 ]. These materials have received considerable attention in the field of nanomaterials, especially in biological imaging [ 8 , 9 ], drug release [ 10 , 11 ], fluorescent probes [ 12 , 13 ], optoelectronic devices [ 14 , 15 ], and other application fields. At present, various methods for synthesizing CDs have been developed, including laser ablation [ 16 ], chemical oxidation [ 17 ], microwave-assisted techniques [ 18 , 19 ], hydrothermal methods [ 20 , 21 ], electrochemical synthesis [ 22 , 23 ], and solution chemistry [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dot based sensors are most commonly based on a fluorescence quenching mechanism induced by the surface states of the carbon dots. On this basis, metal ions such as Ag + [125], Fe 3+ [126], Hg 2+ [127], Cu 2+ [122], Ni 2+ [128] be detected. Ezati et al [129] have devised a method for detecting ammonia and its derivatives using specially prepared carbon dot-containing paper.…”
Section: Application Of Carbon Dots In Food Technologymentioning
confidence: 99%
“…Intensity, specificity, and reliability are the three most crucial factors to consider while investigating sensors. The types of energy transmission that sensors could detect include heat, electric and magnetic, electrochemical and mechanical [70][71][72][73][74]. Due to their extreme sensitivity and selectivity, electrochemical sensors stand out amongst them as particularly interesting analytical techniques.…”
Section: Carbon-based Electrochemical Sensorsmentioning
confidence: 99%